PENGARUH KINERJA DAN KARAKTERISTIK PEMERINTAH DAERAH TERHADAP TINGKAT PENGUNGKAPAN LAPORAN KEUANGAN DI WEBSITE PEMERINTAH DAERAH (Studi Empiris Pemerintah Daerah Daerah Di Provinsi Jawa Timur Tahun 2015-2017) - Aqidatul Firly; Nur Diana; M. Cholid Mawardi (Universitas Islam Malang, 2019)
ABSTRACTThe purpose of this study is to give empirical evidence about the impact of local income, the size of local government, the complexity of local government, and regional expenditure on the level of disclosure of financial statements on the website of regional governments. The sample of this study is the regional government of East Java which discloses the financial statements of local governments on the websites of each local government during 2015-2017, namely as many as 20 local governments. The data analysis method used is logistic regression, because the dependent variable in this study is dummy variable. The results showed that partially the original income variable, local government size, and regional expenditure had a significant positive effect on the level of disclosure of financial statements on the local government website. While the complexity of regional government does not have a significant effect on the level of disclosure of regional financial reports on the local government website. The magnitude of the influence of local revenue, the size of local government, the complexity of local government, and regional expenditure on the level of disclosure of regional financial statements on the local government website is 54%, while the remaining 46% is explained by other variables outside of this regression model.Keywords: Level Of Financial Statement Disclosure, Local Income, Size Of Local Government, Local Government Complexity, Regional Expenditure.